Microstructures, Magnetic Properties and Microwave Absorption Characteristics of Ti2+ -Mn4+Substituted Barium Hexaferrite (Jurnal Elektronika dan Telekomunikasi, 2016)
The effect of Ti2+-Mn4+substitution on microwave absorption has been studied for BaFe12-2xTixMnxO19 ferrite, where x varies from 0.2, 0.4, 0.6 and 0.8.Ti2+-Mn4+ ions were obtained from TiO and MnO2 precursors which were mechanically alloyed together with BaCO3 and Fe2O3 precursors. X-ray diffraction (XRD) patterns for sintered samples confirmed that the materials are consisted with single phase BHF structure. Unit cell volume and crystallite size was found increase with increasing x. Crystallite size for all samples below 70 nm, but the grain morphology shown that the grains is in range of 200 - 400 nm, which concluded that each grain are polycrystalline. The saturation magnetization is increases up to x = 0.4 and decrease for higher x values, while the coercivity remains decreases monotonically. These results were interpreted in terms of the site preferential occupation of Ti2+ and Mn4+ at low level substitution.These substitution revealed of enhanced reflection loss (RL) up to 25 dB forx=0.6.It suggested that the synthesized can be employed as effective microwave absorbers in various devices.